High–Temperature Deformation and Subsequent Static Recrystallization Behavior of Ultra–Low Stacking–Fault Energy Cu–Zn–Si Alloys - Hiromi Miura; Sanshiro Kasuya; Yojiro Oba; Takuya Okada; Chihiro Watanabe; Taworn Benjanarasuth (MATERIALS TRANSACTIONS, 2026)
Behaviors of high–temperature deformation followed by annealing and static recrystallization (SRX) in Cu–Zn–Si alloys with ultra–low stacking–fault energy (SFE) were investigated. The peak stress, steady–state flow stress and grain size during high–temperature deformation appeared to decrease with decreasing SFE, which would suggest easier occurrence of dynamic recrystallization (DRX) with decreasing SFE. Nevertheless, with increasing initial grain size, onset of DRX was much delayed even at higher temperatures and lower strain rates. SRX started after annealing for rather long periods of time contrary to the expectation that SRX should be stimulated because of meta–DRX. New grains evolved by DRX and SRX contained quite high density of annealing twins, showing DRX and SRX mechanisms induced by annealing twin formation during grain–boundary migration.
Keywords: Microstructure and mechanical properties; Shape Memory Alloy Transformations; Metallurgy and Material Forming